Consumo infantil de alimentos industrializados e renda familiar na cidade de São Paulo Association of children's consumption of processed foods and family income in the city of São Paulo, Brazil - Rita de Cássia de Aquino; Sonia Tucunduva Philippi (Universidade de São Paulo, 2002)
OBJETIVO: Descrever o consumo infantil de alimentos industrializados e a relação com a renda familiar per capita, com base em inquérito domiciliar. MÉTODOS: O consumo alimentar de uma amostra probabilística da população infantil residente na cidade de São Paulo, entre zero e 59 meses de idade (n=718), foi estudado em 1995/1996 por meio de inquérito recordatório de 24h. Analisou-se a relação entre o consumo de 24 alimentos industrializados e a renda familiar per capita, distribuída em quartis. RESULTADOS: O consumo de açúcar foi maior entre as crianças de menor renda, enquanto achocolatados, chocolates, iogurte, leite em pó modificado e refrigerantes foram mais consumidos por crianças de maior renda familiar per capita (p<0,05). CONCLUSÕES: Concluiu-se que a renda familiar per capita influencia o consumo de alguns alimentos industrializados. OBJECTIVE: To describe children's consumption of processed foods and its relationship with per capita family income based on a household survey. METHODS: Food consumption was studied in a statistical sample of 718 children living in the city of São Paulo in the period 1995-1996. A 24-hour dietary recall was used. Data regarding the association of children's consumption of 24 processed foods and per capita family income (arranged in quartiles) was analyzed. RESULTS: Consumption of sugar was higher among children of low income families whereas the consumption of chocolate powder, chocolate, yogurt, infant formula and soft drinks was higher among children of high income families (p< 0.05). CONCLUSIONS: It seems that per capita family income affects the consumption of some processed foods.